Le Leucaena leucocephala et les Bas de l’Ouest à l’île de La Réunion - Morgane Robert (Projets de Paysage)
This article, based on doctoral research, proposes to lay the groundwork for a new interpretation of the processes at work in the landscapes of the savannahs and ravines on the leeward side of Reunion Island, under 400 metres in altitude. A plant-based approach intended to demonstrate that the reconstruction of a landscape’s history may be partly correlated with the trajectory of a particular plant species in that landscape. This trajectory is built around the changes in the interrelations between the plant, a society and different environments. The history of Leucaena leucocephala, now considered to be one of the major invasive alien species in the savannahs and gullies of the western slopes of the Island, will be central here; it will show the link between the decline in the uses made of the plant and its propagation dynamics.